Acne calcified scars: Case report - Sá, Mara Aparecida Barbosa de; Simoes, Natália Myrra; Rodrigues, Eduardo Silveira; Cardoso, Claudia Assunçao e Alves; Silva, Amaro Ilidio Vespasiano; Manzi, Flávio Ricardo (Journal of Oral Diagnosis, 2018)
Introduction: The involvement of calcium regulatory factors in the epithelial tissue can result in calcification or cutaneous ossification. The secondary osteomas, wherein the calcification develops in a preexisting skin lesions such as acne, for example, are the most common. Objective: To report a case of calcification/ossification of soft tissues compat- ible with acne scarring. Case report: Panoramic panoramic radiographic examination revealed radiopaque, circular image in the alveolar ridge region in the air corresponding to tooth 36, with residual root characteristics . The alteration in the diagnostic hypothesis occurred after periapical radiography, which revealed a displacement of the radiopaque image to the upper region of the border, confirmed by another radiograph with a film placed in the position between the vestibular face of the alveolar border and the mucosa of the cheek. Conclusion: The radiographic findings associated with anamnesis and clini- cal examination suggested a diagnosis ofcalcification/ossification in soft tissue compatible with the healing of acne.